The Influence of Service Quality, Customer Experience, and Brand Image on Customer Satisfaction at Baita Car Wash in Gresik City - Syahputra, Denny; Dermawan, Rizky (PT Inovasi Pratama Internasional, 2025)
This study aims to analyze the influence of service quality, customer experience, and brand image on customer satisfaction at Baita Car Wash in Gresik City using a quantitative approach. A total of 150 respondents were selected using the accidental sampling technique, namely customers who were encountered by chance during the research and met the study criteria. Data were analyzed using Structural Equation Modeling (SEM) Partial Least Squares (PLS) with SmartPLS 3 software. The results indicate that service quality, customer experience, and brand image have a positive and significant effect on customer satisfaction, demonstrating their crucial role in enhancing customer satisfaction.